1999
DOI: 10.1021/es9906756
|View full text |Cite
|
Sign up to set email alerts
|

The Predominance of Inorganic Arsenic Species in Plants from Yellowknife, Northwest Territories, Canada

Abstract: Elevated levels of arsenic in Yellowknife, NWT, Canada, from historic and recent gold mine operations, are of increasing concern to Yellowknife residents. The study of arsenic in Yellowknife plants is a part of ongoing bioavailability and food chain research. A variety of plants from Yellowknife were analyzed for total arsenic and water soluble arsenic species. The plants included vascular plants and bryophytes (mosses). Total amounts of arsenic were greatest in mosses and varied greatly within specimens of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
76
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(89 citation statements)
references
References 25 publications
12
76
0
1
Order By: Relevance
“…Similar to other studies on higher plants (e.g. Koch et al, 2000;Quaghebeur and Rengel, 2003;Raab et al, 2005;Xu et al, 2007), we found arsenite and arsenate to be the dominant forms of As in the two strains of Azolla, with methylated As compounds accounting for <5% of the total As. However, the two Azolla strains showed a significant difference in the proportions of arsenite versus arsenate, with A. filiculoides having a higher percentage of arsenite (55-70%) than A. caroliniana (25-40%) (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to other studies on higher plants (e.g. Koch et al, 2000;Quaghebeur and Rengel, 2003;Raab et al, 2005;Xu et al, 2007), we found arsenite and arsenate to be the dominant forms of As in the two strains of Azolla, with methylated As compounds accounting for <5% of the total As. However, the two Azolla strains showed a significant difference in the proportions of arsenite versus arsenate, with A. filiculoides having a higher percentage of arsenite (55-70%) than A. caroliniana (25-40%) (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…A small percentage of As may also be transformed into organic species such as methylated As compounds and arsenosugars (Koch et al, 2000). Similar to other studies on higher plants (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Arsenic was almost quantitatively extracted from the samples with the lowest total arsenic concentration, whereas in the samples with the highest total arsenic concentration less than 25% was extractable. In the case of aboveground plant biomass, poor extractability of arsenic compounds not exceeding 50% of total arsenic content was observed similarly as in our previous experiments [34] and reported by other authors [44]. Similarly, Ruiz-Chancho et al [45] reported extraction efficiencies ranging from 3.0% to 41.4%, with good agreement between samples from the same plant species where different extraction procedures with different ratios of water and methanol were compared.…”
Section: Contents Of Investigated Elements and Arsenic Compounds In Rsupporting
confidence: 89%
“…Therefore, the abundance and distribution of arsenic compounds within red beet plants did not differ significantly from the behavior of arsenic compounds in other plant species and the results were expectable. Comparable results have been presented by other authors within different plant species [16,19,20,44].…”
Section: Contents Of Investigated Elements and Arsenic Compounds In Rsupporting
confidence: 85%
“…A small percentage of organic compounds of As have been reported, for example in stems and leaves of pepper plants [20], and have been described by other authors in many different plant species [29,30], but were not detected in the mint samples. In the case of aboveground plant biomass, poor extractability of As compounds (not exceeding 50% of total As concentration) has been reported previously [20,31]. The results can be affected by the presence of As-phytochelatin complexes found in various plant species [6,32,33].…”
Section: C) Standard Deviation Was Not Calculated Because Of Low Numbmentioning
confidence: 84%